Clinico pathological study of hysterecomy for benign conditions of the uterus - KL, Sucheta; KP, Madhu; Manangi, Mallikarjuna; BJ, Arun; Nagaraj, Niranjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Uterus, being a vital female reproductive organ is subjected to many different pathological conditions. The objective was to study the correlation between the preoperative clinical diagnosis and the final histopathology of hysterectomy specimens. Methods: This is a retrospective study by the authors of all cases who underwent a hysterectomy over a 2 year period (2012-2014). All hysterectomies performed for malignant indication were excluded. The specimen was sent for histopathology examination to the pathology department of Vanivilas Hospital and Bowring and Lady Curzon Hospital, Bangalore, India. All hysterectomy specimens were fixed in 10% buffered formalin, paraffin embedded and 4-5μm thick sections were cut and stained with haematoxylin and eosin. All the collected data was tabulated and stastically analyzed by using SPSS software. Results: During the 2 year study period there were a total of 200 cases eligible for analysis. Leiomyoma was reported in 31% of specimen. Adenomyosis was reported in 20% of present cases. Chronic cervicitis was observed in 51% of cases in present study. Endometritis was observed in 3% of cases in present study. Tubercular endometritis was observed in 0.5% of cases. Endometrial polyp was observed in 1% of case in this study. 10% of the specimen was unremarkable and no pathology could be found. Conclusions: All hysterectomy specimens should be sent for histopathology regardless of the preoperative histopathology of the endometrium.